Transformers - Bay, Michael, 1964-; Di Bonaventura, Lorenzo; Paramount Pictures Corporation; Dreamworks Pictures (United States : Paramount Pictures, 2007)
A war re-erupts on Earth between two robotic clans, the heroic Autobots and the evil Decepticons, leaving the fate of mankind hanging in the balance
Title from title screen
Executive producers, Steven Spielberg, Michael Bay, Brian Goldner, Mark Vahradian ; camera, Mitchell Amundsen ; editing, Paul Rubell, Glen Scantlebury, Thomas A. Muldoon ; music, Steve Jablonsky ; animation supervisor, Scott Benza
Cast: Shia LaBeouf, Megan Fox, Josh Duhamel, Tyrese Gibson, Rachael Taylor, Anthony Anderson, Jon Voight, John Turturro
Voices : Peter Cullen, Mark Ryan
VCD Format
With Malay and Chinese subtitles
Keywords: Transformers (Fictitious characters) -- Drama; alismans -- Drama